Rancang Bangun Aplikasi Manajemen Rapat Kerja Berbasis Web - Dani Yusuf (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2023)
This research aims to produce an output in the form of an application that functions to manage work meeting activities in an organization, whether formal, government, private or non-formal institutions. The research was conducted at the Faculty of Computer Science, Bhayangkara University, Jakarta Raya, from January 2023 to November 2023. Work meetings are staff meetings to discuss matters related to the implementation of work duties within an agency, organization or company. In this work meeting, it is necessary to record the costs incurred for meeting activities, document and archive them for administrative purposes as well as supporting evidence for an activity. Based on researchers' observations, minutes of work meeting activities, including attendance of work meeting participants, are still done manually, namely recorded using MS Word or Excel, so the data is often difficult to obtain or takes a long time to find. Based on these problems, it is necessary to have an application that can manage recaps of work meeting activities such as meeting minutes, meeting participants and photo documentation in real time, so that all meeting participants can know the results of the meeting directly. The system development method in this research is using the prototype method, the application is developed using the native PHP programming language and the database used is MySQL. The application created is expected to help government, private and other agencies in managing work meeting activity data optimally.